Auditive Raume des alten Agypten : die Umgestaltung einer Horkultur in der Amarnazeit - Meyer-Dietrich, Erika. (Culture and History of the Ancient Near East, 2017)
In Auditive Räume des alten Ägypten Erika Meyer-Dietrich explores the sonic aspects of culture in the 18th Dynasty (1550-1290 BCE). Crucial to the transformation of an audio culture during the Amarna Period are the transfer of traditional sound patterns to new contexts and the position of the heard body in social spaces. Based on the iconography of sonic acting and the representation of urban places as auditive spaces in the rock tombs of Tell el Amarna she convincingly shows how, through sound sequences and the creation or omission of sounds, auditive spaces are given social and religious significance. Her work adds an important new aspect to the understanding of the Amarna Period, which until now has been studied mainly as a visual culture.